2020
DOI: 10.1371/journal.pone.0241588
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin injection without electromyographic guidance in consecutive esotropia

Abstract: Purpose To investigate the efficacy of botulinum toxin injection without electromyographic guidance for the treatment of consecutive esotropia. Methods A retrospective study was performed on 49 subjects with consecutive esotropia who received botulinum toxin injection in the medial rectus muscles without the use of electromyographic guidance. Treatment was considered successful if the final ocular alignment was orthotropic or esodeviation was ≤10 prism diopters (PD) during distant fixation. Results The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Concerning safety issues, even though it has been reported that BT injection may cause potential complications, such as ptosis, vertical deviation, subconjunctival or retrobulbar hemorrhage, scleral penetration, and systemic allergic reaction (43)(44)(45)(46)(47), our patients well tolerated the procedure, not presenting with serious or permanent complications, but only transient ptosis (40% of cases).…”
Section: Discussionmentioning
confidence: 75%
“…Concerning safety issues, even though it has been reported that BT injection may cause potential complications, such as ptosis, vertical deviation, subconjunctival or retrobulbar hemorrhage, scleral penetration, and systemic allergic reaction (43)(44)(45)(46)(47), our patients well tolerated the procedure, not presenting with serious or permanent complications, but only transient ptosis (40% of cases).…”
Section: Discussionmentioning
confidence: 75%
“…Initial overcorrections were managed conservatively with monocular patching, full hyperopic correction, bifocal glasses, topical anticholinesterase, botulinum toxin, or base-out prisms [28,[116][117][118][119]. Kim and Choi [115] reported that the divergence-excess type X (T), amblyopia, BLR, esodeviation ≥ 20 PD at postoperative day 1, younger age at diagnosis and surgery, and shorter duration from onset to surgery Surgical Treatment of Intermittent Exotropia were risk factors for consecutive esotropia.…”
Section: Xiii-2 Management Of Consecutive Esotropiamentioning
confidence: 99%
“…Another option for managing the persistent consecutive esotropia could be botulinum toxin injection with/without electromyographic guidance. Yang et al [119] revealed that initial postoperative esodeviation of ≤ 18 PD at 1 month after exotropia surgery was a predictor for success. Vertical deviation and/or ptosis occurred in 8% of the patients and resolved within 3 months.…”
Section: Xiii-2 Management Of Consecutive Esotropiamentioning
confidence: 99%
See 1 more Smart Citation